Probing the ballistic microcirculation in placenta using flow‐compensated and non‐compensated intravoxel incoherent motion imaging. Issue 1 (27th July 2020) - Jiang, Ling; Sun, Taotao; Liao, Yuhao; Sun, Yi; Qian, Zhaoxia; Zhang, Yi; Wu, Dan
Abstract : Purpose: Intravoxel incoherent motion (IVIM) imaging is widely used to evaluate microcirculatory flow, which consists of diffusive and ballistic flow components. We proposed a joint use of flow‐compensated (FC) and non‐compensated (NC) diffusion gradients to probe the fraction and velocity of ballistic flow in the placenta. Methods: Forty pregnant women were included in this study and scanned on a 1.5T clinical scanner. FC and NC diffusion MRI (dMRI) sequences were achieved using a pair of identical or mirrored bipolar gradients. A joint FC‐NC model was established to estimate the fraction ( fb ) and velocity ( vb ) of the ballistic flow. Conventional IVIM parameters ( f, D, and D *) were obtained from the FC and NC data, separately. The vb and f · D *, as placental flow velocity measurements, were correlated with the umbilical‐artery Doppler ultrasound indices and gestational ages. Results: The ballistic flow component can be observed from the difference between the FC and NC dMRI signal decay curves. vb fitted from the FC‐NC model showed strong correlations with umbilical‐artery impedance indices, the systolic‐to‐diastolic (SD) ratio and pulsatility index (PI), with correlation coefficients of 0.65 and 0.62. The f · D * estimated from the NC data positively correlated with SD and PI, while the FC‐based f · D * values showed weak negative correlations. Significant gestational‐age dependence was also found in the flow velocity measurements. Conclusion: Our results demonstrated the feasibility of using FC and NC dMRI to noninvasively measure ballistic flow velocity in the placenta, which may be used as a new marker to evaluate placenta microcirculation.